Early expressive and receptive language trajectories in high-risk infant siblings of children with autism spectrum disorder. (November 2017) - Longard, Julie; Brian, Jessica; Zwaigenbaum, Lonnie; Duku, Eric; Moore, Chris; Smith, Isabel M; Garon, Nancy; Szatmari, Peter; Vaillancourt, Tracy; Bryson, Susan
Background & aims: In response to limited research on early language development in infants at high risk for Autism Spectrum Disorder (ASD), the current prospective study examined early expressive and receptive language trajectories in familial high-risk (HR) infants who were and were not later diagnosed with ASD (HR-ASD and HR-N, respectively), and low-risk (LR) controls with no family history of ASD. Methods: Participants were 523 children (371 HR siblings, 56% boys; 152 LR controls, 52% boys) followed from age 6 or 12 months to 36 months. Based on independent, best-estimate clinical diagnoses at 36 months, HR participants were classified as HR-ASD (n = 94; 69% boys), or HR-N (n = 277; 52% boys); the sample also included 152 LR controls (52% boys). Expressive and receptive language trajectories were examined based on corresponding domain standard scores on the Mullen Scales of Early Learning ( MSEL ) at 6, 12, 24, and 36 months. In the combined sample of HR and LR infants, semi-parametric group-based modeling was used to identify distinct trajectories in MSEL standard scores. Results: A 3-group solution provided optimal fit to variation in both expressive and receptive language, with the following patterns of scores: (1) inclining from average to above average, (2) stable-average, and (3) declining from average to well below average. For both expressive and receptive language, membership in these trajectories was related to 3-year diagnostic outcomes. Conclusions: Although HR-ASD, HR-N, and LR control infants were in each trajectory group, membership in the declining trajectory (expressive and/or receptive) was associated with an ASD diagnosis. Implications: Evidence of declining trajectories in either expressive or receptive language may be a risk marker for ASD in a high-risk sample.